PENERAPAN SISTEM ERP (ENTERPRISE RESOURCE PLANNING) WAREHOUSE MANAGEMENT DALAM MENINGKATKAN KINERJA PERUSAHAAN - Puji Rahayu; Vera Yanti Tambunan; Merry Agutina; Windy Anastasya; Decci Japin; Diva Melinda (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
ERP (Enterprise Resource Planning) is a science concept that integrates data, information and business processes to manage the internal and external resources of a company. Many ERP concepts have been developed to facilitate data integration. One of them is the use of an ERP warehouse management module that is applied to the company's business processes. One of the functions of the company's warehouse is to know some important aspects that can be very helpful in improving company performance. This study uses the Warehouse Management module. The results will help you correctly and accurately document your company's warehousing capabilities and resolve any issues.